2021
DOI: 10.3390/jpm11070608
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Health Care for Older Diabetes Patients from the Perspective of Health Professionals and Service Consumers

Abstract: Background: Individualized nursing care as a form of person-centered care delivery is a well-known approach in the health care context and is accepted as best practice by organizations and professionals, yet its implementation in everyday practice creates serious challenges. The aim was to assess and compare the perceptions of health professionals and older diabetes patients on their individual care in regard to the patient’s clinical situation, personal life situation, and decisional control. Methods: The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…By all definitions, open discussion with patients about how they are taking their medication is crucial. Previous studies have demonstrated the benefits of patient-centered care and the association it has with empowerment and adherence [13,[60][61][62][63]. Healthcare and research teams could explore ways to provide individual patients with appropriate parameters for adjusting or strategically managing treatment regimens as needed.…”
Section: Discussionmentioning
confidence: 99%
“…By all definitions, open discussion with patients about how they are taking their medication is crucial. Previous studies have demonstrated the benefits of patient-centered care and the association it has with empowerment and adherence [13,[60][61][62][63]. Healthcare and research teams could explore ways to provide individual patients with appropriate parameters for adjusting or strategically managing treatment regimens as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed results about the assessments of individuality in care of Lithuanian older patients with diabetes were reported previously (Bartkeviciute et al, 2021). This paper presents an analysis of effective health communication, psychosocial self-efficacy of patients, access to diabetes-related resources and support and socio-demographics as they relate to the individualized care of older patients with diabetes mellitus.…”
Section: Re Sultsmentioning
confidence: 96%
“…The Communication Assessment Tool (CAT), The Diabetes Empowerment Scale (DES) and The Resources and Support for Self-Management scale (RSSM) were translated into the Lithuanian language and back again into English (Maneesriwongul & Dixon, 2004). Validation of the ICS patient version in Lithuanian was reported in a previous publication (Bartkeviciute et al, 2021).…”
Section: Instrumentsmentioning
confidence: 99%
“…It is imperative to hear and respect patients’ voices and incorporate multidimensional therapies targeting biological and psychological pains concordantly [ 27 , 28 , 29 ]. Research in rheumatology and other medical disciplines have predominately evaluated the patients’ conditions quantitatively [ 30 , 31 ]. This study utilized qualitative methods to uncover and synthesize lesser-understood psychological burdens, whether from or in combination with physical encumbrances.…”
Section: Introductionmentioning
confidence: 99%